ASEAN economic growth, trade openness and banking-sector depth: The nexus - Rudra P. Pradhan; Mak B. Arvin; John H. Hall; Neville R. Norman (EconomiA, 2017)
This paper investigated the linkages between banking sector depth, trade openness, and economic growth using a panel data set covering the ASEAN regional forum countries for the period 1961–2012. Using our multivariate framework, we first found that all the variables were integrated of order one and were cointegrated. Our panel-data estimation procedures offered more robust estimates than previous studies by utilizing variations between countries as well as variations over time. The results of this study indicated a general long-run equilibrium relationship among trade openness, banking sector depth and economic growth as well as a short-run relationship between these variables. Policy recommendations include those that will promote greater banking sector development as well as increased trade openness.
Keywords: 330; Trade openness; Banking sector depth; Economic growth; Granger causality; ASEAN regional forum countries